Mulheres na gestão pública: um estudo de caso na Universidade Federal da Paraíba – Campus II - Santos, Ivandro José Candido dos (2021)
Woman’s actuation, in all spheres of society, has widened in the last decades, with important achievements, resulting from an intense agenda of actions. However, studies about gender relations prove that the feminine presence did not have the expected increase when the matter is management positions. The present research investigated women’s participation and representation in management positions established by the Agrarian Sciences Center (ASC), Campus II, at Universidade Federal da Paraíba (UFPB), institution, founded in 1936 and which, till the year of 1976, offered only the Agronomy course, considered as a masculine course. Along this period, the Patriarchate and androcentrism were even more evident on the culture and history. A case study was carried out based on gender relations. Efforts have been made to understand the elements that provoke gender-based inequality in ASC/UFPB management positions, building up a mapping of the female participation in the aforementioned institution, in the period of 2010 to 2020. It was made a diagnosis of the management positions, presenting the comparative between the proportion of women and men acting in ASC as well as the means that translate the feminine participation and the management positions access conditions. This study was justified by the low number of women in positions of high hierarchy around the world, by the importance of considering the subject so that more persons will know about it and either by the shortage of studies concerning to the feminine management in the educational context, more specifically, in a Public Higher School Institution at Paraíba. The study found that, comparing permanent members of the campus, the number of men was greater than the number of women in the categories of professor administrative technique, as well as in the occupation of higher positions posts in the hierarchy and those, which are eligible for receiving a gratification. Were identified barriers that, in general, women encounter in their professional career in the institution and it makes them, although are increasingly present, have difficulty in the access and permanence in the management post of ASC/UFPB. This work results in the presentation of demands and actions suggested by the participants to the ASC Direction and in the elaboration of the “Gender Equality Booklet”.